The Impact of Social Work Supervision on Interns' Employment Intention: New Evidence from Mainland China. - Lan, Zhensong; Mu, Liping; Qiu, Xue; Liu, Huaqiang; Huang, Xuefang (British Journal of Social Work, 2024)
Supervision is a key link in social work practice and plays an important role in the cultivation of social work professionals. This study investigated the impact of social work internship supervision on the employment intention of 271 social work interns from five universities in Guangxi, China. The results show that the employment intention of male students is higher than that of female students, and the employment intention of interns with urban household registration is higher than that of interns with rural household registration; internship investment and school–enterprise cooperation have a positive impact on the exertion of the supervision function, but internship investment plays a full mediating role between the supervision function and employment intention, whilst school–enterprise cooperation regulates the relationship between the supervision function and internship investment. Real factors, such as economy and social status, continue to be important factors influencing social work students' employment intention. When conducting social work internship educational activities, schools should create a favourable internship environment and working conditions for interns and maintain good cooperation with internship organisations. This will facilitate internship supervision and enhance employment intention.